Silk fibroin / hydroxyapatite composite material as well as preparation method and application thereof
During the preparation of silk fibroin/hydroxyapatite composite material, using a soft porous plug wrapped in dialysis membrane to apply constant thrust and solvent exchange regeneration, the problem of insufficient overall strength of the material is solved and its mechanical properties are significantly improved. Suitable for fracture fixation and bone repair.
Patent Information
- Application Number
- CN202411245935.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-24
AI Technical Summary
The overall strength of existing silk fibroin/hydroxyapatite composites is insufficient, making it difficult to meet the mechanical properties requirements of fracture fixation and bone repair.
A soft porous plug wrapped in dialysis membrane applies constant thrust to the mold opening, and through exchange regeneration of methanol and hexafluoroisopropanol, silk fibroin molding and increase density, thereby improving the mechanical properties of the composite material.
The three-point bending strength and tensile fracture resistance of the silk fibroin/hydroxyapatite composite material were significantly improved, reaching 235N and 153MPa, which was better than the same-sized bone nails prepared by traditional molding methods.
Smart Images

Figure CN119174847A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical materials and relates to a silk fibroin / hydroxyapatite composite material and a preparation method and application thereof. Background Art
[0002] Fracture is a common bone injury disease in clinical practice, accounting for a high proportion in trauma surgery. For this type of bone injury disease, the main treatment in clinical practice is to implant fracture fixation materials at the injury site through surgical operations. The fracture ends are directly fixed surgically using internal fixation materials such as bone plates, screws, and intramedullary nails to fix and repair damaged bone tissue. Good fracture internal fixation materials should meet the following conditions: ① good biocompatibility; ② stable fixation strength; ③ no complications and can promote fracture healing.
[0003] At present, bioactive metal materials used for fracture fixation and bone repair mainly include high-quality stainless steel and titanium alloys. These materials have high mechanical strength and fracture resistance, but the metal ions released by corrosion or wear in the body can induce a series of adverse reactions, thereby greatly reducing their biocompatibility. In addition, there are significant differences in the elastic modulus and tensile strength between metal and bone tissue, which will produce a significant stress shielding effect, leading to weakening of the strength of the surrounding bone tissue and fracture. Therefore, after the fracture is completely healed, a secondary operation is required to remove the metal fixation, which causes great pain to the patient. Biodegradable implant materials can replace traditional inert metal implants, reduce trauma to patients, reduce medical costs, and avoid secondary operations. At present, the degradable fracture internal fixation materials on the market are mainly polylactic acid, but the degradation products of polylactic acid have certain corrosiveness to bone tissue, leading to the occurrence of inflammatory reactions at the site of bone injury.
[0004] Silk fibroin is a natural polymer extracted from silk, a high-purity protein that is rich in 18 kinds of amino acids. It has good biocompatibility and biodegradability. The degradation products of silk fibroin in the body are amino acids and peptides, which are non-toxic to the human body. It can also promote the metabolism of cells in the wound site, thereby promoting the repair of tissues.
[0005] Nano-hydroxyapatite is an inorganic nanoparticle and the main inorganic component of human bones. It has good biocompatibility and bioactivity, is inexpensive, and has stable properties. It is widely used in the field of bone tissue repair. Hydroxyapatite can achieve chemical bonds with body tissues at the interface to achieve complete affinity with the matrix. In addition, hydroxyapatite has a certain solubility in the body, releasing calcium, phosphorus and other elements that are beneficial to the human body, directly participating in human metabolism, and thus promoting the repair of defective bone tissue.
[0006] Chinese patent document CN113332498A (publication date: September 3, 2021) discloses a method for preparing a silk fibroin / hydroxyapatite composite material, which first pours a mixture of hydroxyapatite nanoparticles, silk fibroin, and hexafluoroisopropanol into a long cylindrical mold, keeps the upper end open and stands in methanol, and then turns the upper and lower ends over and continues to stand after preliminary molding; finally, remove the mold, ventilate and dry, and obtain a silk fibroin / hydroxyapatite composite material. Although the silk fibroin / hydroxyapatite composite material has uniform strength and good mechanical properties, its overall strength needs to be further improved. Summary of the invention
[0007] The invention provides a silk fibroin / hydroxyapatite composite material and a preparation method and application thereof, aiming to improve the overall strength of the silk fibroin / hydroxyapatite composite material.
[0008] In order to achieve the above invention objectives, the present invention pours the precursor solution into a long cylindrical mold with one end open and the other end closed, and then seals the open end of the mold with a soft porous plug wrapped by a dialysis membrane. While the mold is statically formed in methanol, a peristaltic pressurizing device is used to apply a constant thrust of a certain magnitude to the soft porous plug wrapped by the dialysis membrane. As the silk fibroin in the mold gradually takes shape and shrinks in volume, the sealed sponge plug is also squeezed inwardly under the action of the external thrust, so that the unformed silk fibroin molecules in the mold are more densely stacked. At the same time, the soft porous plug wrapped by the dialysis membrane allows methanol and hexafluoroisopropanol to pass through and freely enter and exit the mold. The unformed part of the silk fibroin continues to exchange and regenerate with methanol, and finally a silk fibroin / hydroxyapatite composite material with better mechanical properties is obtained.
[0009] The technical solution provided by the present invention is specifically as follows:
[0010] The first aspect of the present invention provides a method for preparing a silk fibroin / hydroxyapatite composite material, comprising the following steps:
[0011] Providing a precursor solution; the precursor solution consists of inorganic nanoparticles, silk fibroin and hexafluoroisopropanol; the inorganic nanoparticles are hydroxyapatite nanoparticles or a mixture of hydroxyapatite nanoparticles and zinc oxide nanoparticles;
[0012] The precursor solution is poured into a long cylindrical mold with one end open and the other end closed, and then the open end of the mold is sealed with a soft porous plug wrapped with a dialysis membrane;
[0013] The mold is horizontally immersed in methanol for at least 4 days, during which a constant thrust of 30 to 300 N is applied to the porous plug wrapped with the dialysis membrane, the soft porous plug wrapped with the dialysis membrane is evenly and slowly pushed into the mold, and the mold is turned upside down 180 degrees every 2 to 4 hours to obtain a molded body;
[0014] The mold is removed, and the molded body is immersed in pure water for at least 7 days. After drying at room temperature, a silk fibroin / hydroxyapatite composite material is obtained.
[0015] In some embodiments of the present invention, the dialysis membrane has a molecular weight cut-off of 5 to 15 kDa.
[0016] In some implementations of the present invention, the constant thrust is 30-50N.
[0017] In some embodiments of the present invention, in the precursor solution, the ratio of the total amount of inorganic nanoparticles to hexafluoroisopropanol is 30-40 g:100 mL; and / or, the hydroxyapatite nanoparticles account for 1wt% to 55wt% of the total amount of silk fibroin and inorganic nanoparticles; the silk fibroin accounts for 45wt% to 99wt% of the total amount of silk fibroin and inorganic nanoparticles.
[0018] In some embodiments of the present invention, the hydroxyapatite nanoparticles account for 20 wt% to 30 wt% of the total amount of silk fibroin and inorganic nanoparticles; the silk fibroin accounts for 70 wt% to 80 wt% of the total amount of silk fibroin and inorganic nanoparticles.
[0019] In some embodiments of the present invention, providing a precursor solution comprises:
[0020] Silk fibroin and inorganic nanoparticles are added to hexafluoroisopropanol, mixed and allowed to stand for more than 0.5 h in an environment of 50-60° C., and bubbles are removed after the solid is completely dissolved to obtain a precursor solution.
[0021] In some embodiments of the present invention, the particle size of the hydroxyapatite nanoparticles is 60 to 80 nm; the particle size of the silk fibroin is 0.1 to 1.5 mm.
[0022] In some embodiments of the present invention, the precursor solution further comprises a functional factor, which is one or more of curcumin, vancomycin, astragalus polysaccharide, and gentamicin, and the weight percentage of the functional factor in the silk fibroin / hydroxyapatite composite material is 0.1% to 5%.
[0023] The second aspect of the present invention provides a silk fibroin / hydroxyapatite composite material prepared by the preparation method of the silk fibroin / hydroxyapatite composite material.
[0024] The third aspect of the present invention provides the use of the silk fibroin / hydroxyapatite composite material in the preparation of bone repair parts.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0026] The three-point bending strength of a bone nail with a length of 150 mm prepared from the hydroxyapatite / silk fibroin composite material of the present invention can reach 235N, and the tensile fracture strength can reach 153MPa. The mechanical properties are significantly better than those of a bone nail of the same size processed from a hydroxyapatite / silk fibroin composite material prepared by an existing molding method. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 : Schematic diagram of the dialysis membrane-wrapped sponge plug.
[0028] Figure 2 : Schematic diagram of the present invention applying a constant thrust to a sponge plug wrapped with a dialysis membrane.
[0029] Figure 3 : Product picture of the semi-threaded screw of the present invention.
[0030] Figure 4 Example 1: Maximum deformation force and tensile strength of 150 mm long bone screws processed from hydroxyapatite / silk fibroin composite materials prepared under different constant thrusts.
[0031] Figure 5 : Comparison of three-point bending and tensile strength of 150 mm long bone screws made of hydroxyapatite / silk fibroin composite materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2 under a constant thrust of 30 N.
[0032] Figure 6 : Scanning electron microscope (SEM) image of the hydroxyapatite / silk fibroin composite material prepared in Example 1 under a constant thrust of 30N.
[0033] Figure 7 : The antibacterial rate of the hydroxyapatite / silk fibroin composite material prepared in Example 2. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] For simplicity, the present invention only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range. Similarly, any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0036] It should be noted that, in the description of the present invention, unless otherwise specified, "above" and "below" are inclusive numbers, and the meaning of "multiple" in "one or more" is two or more. Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements.
[0037] In the description of the present invention, the description with reference to the terms "any embodiment / method", "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments / methods or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, without contradiction.
[0038] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. These embodiments can be used in various combinations. In each example, the enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0039] Preparation method:
[0040] As described in the background technology, in the prior art, a long cylindrical mold filled with a precursor solution is placed vertically in methanol, with the upper end kept open and placed in methanol. After initial forming, the upper and lower ends are turned over and continued to be placed. The overall strength of the prepared silk fibroin / hydroxyapatite composite material needs to be further improved.
[0041] In order to improve the overall strength of a silk fibroin / hydroxyapatite composite material, the present invention provides a method for preparing a silk fibroin / hydroxyapatite composite material, comprising the following steps:
[0042] Providing a precursor solution; the precursor solution consists of inorganic nanoparticles, silk fibroin and hexafluoroisopropanol;
[0043] The precursor solution is poured into a long cylindrical mold with one end open and the other end closed, and then the open end of the mold is sealed with a soft porous plug wrapped with a dialysis membrane;
[0044] The mold is horizontally immersed in methanol for at least 4 days, during which a constant thrust of 30 to 300 N is applied to the porous plug wrapped with the dialysis membrane, the soft porous plug wrapped with the dialysis membrane is evenly and slowly pushed into the mold, and the mold is turned upside down 180 degrees every 2 to 4 hours to obtain a molded body;
[0045] The mold is removed, and the molded body is immersed in pure water for at least 7 days. After drying at room temperature, a silk fibroin / hydroxyapatite composite material is obtained.
[0046] According to the preparation method of the present invention, during the solvent exchange between methanol and hexafluoroisopropanol, the soft porous plug wrapped by the dialysis membrane is evenly and slowly pushed into the mold, and as the silk fibroin in the mold is gradually formed and the volume shrinks, the soft porous plug wrapped by the dialysis membrane is also squeezed inwardly under the action of a constant thrust, so that the unformed silk fibroin molecules in the mold are more densely stacked, and at the same time, the soft porous plug wrapped by the dialysis membrane allows methanol and hexafluoroisopropanol to pass through and freely enter and exit the mold, and the unformed part of the silk fibroin continues to exchange and regenerate with methanol, and finally a silk fibroin / hydroxyapatite composite material with better mechanical properties is obtained.
[0047] In the prior art, the upper end of the long cylindrical mold is open and the lower end is closed. The long cylindrical mold is placed vertically and turned upside down after standing for a period of time. The inventor conducted in-depth research and found that when the long cylindrical mold is placed vertically, the material is gradually formed downward from the upper end opening. After the flipping operation, the unformed solution will shear each other to form internal bubbles, thereby making the silk fibroin / hydroxyapatite composite material have poor mechanical properties. The present invention places the long cylindrical mold horizontally, and inserts a soft porous plug that can slide along the cylinder wall and allow the solvent to enter and exit freely but does not allow silk fibroin and inorganic nanoparticles to enter and exit at one end of the opening. During the standing process, the composite material is gradually formed inward from one end of the opening. Since the composite material forming process is slow, the present invention flips the mold up and down 180° every 2 to 4 hours to avoid the agglomeration and sedimentation of the precursor solution. The upside-down flipping process does not cause the unformed solution and the formed composite material to shear each other, and since the unformed solution is relatively viscous, the upside-down flipping process will not cause the connection between the unformed solution and the formed composite material to be twisted. Therefore, compared with the prior art, the present application finally obtains a silk fibroin / hydroxyapatite composite material with better mechanical properties.
[0048] In some embodiments of the present invention, the cross-section of the long cylindrical mold is one or a combination of rectangular, circular, elliptical, trapezoidal, and oval.
[0049] In some embodiments of the present invention, the long cylindrical mold is a test tube, preferably a plastic test tube; the soft porous plug is a sponge plug, preferably. The test tube is closed at one end and open at the other end, and has a smooth inner wall, allowing the sponge plug to slide along the inner wall. Preferably, the dialysis membrane wraps the sponge plug. Preferably, the molecular weight cutoff of the dialysis membrane is 5 to 15 kDa. The dialysis membrane with a molecular weight cutoff within the above range allows methanol and hexafluoroisopropanol to pass through, but does not allow hydroxyapatite nanoparticles and silk fibroin to pass through, which can prevent hydroxyapatite nanoparticles and silk fibroin from flowing out of the mold and causing the volume of the molded body to fail to reach the target size.
[0050] The present invention applies a constant thrust of 30 to 300 N to the soft porous plug wrapped by the dialysis membrane, which can ensure that the soft porous plug is pushed into the mold while the silk fibroin / hydroxyapatite composite material shrinks, and then pressurizes one end of the silk fibroin / hydroxyapatite composite material to make the silk fibroin / hydroxyapatite composite material dense. Preferably, the constant thrust is 30 to 50 N. If the thrust is too large, the soft porous plug will be pushed into the mold too fast, causing pressure on the material before the silk fibroin / hydroxyapatite composite material is formed, affecting the final mechanical properties of the product; if the thrust is too small, the silk fibroin / hydroxyapatite composite material formed will be loose inside and have poor mechanical properties.
[0051] In some embodiments of the present invention, removing the mold includes: pouring the molded body out of one end of the mold opening. The silk fibroin / hydroxyapatite composite material shrinks during the molding process, so there is a certain gap between the molded body and the inner wall of the mold, and the molded body can be easily poured out of one end of the mold opening, and the mold can be reused.
[0052] In some embodiments of the present invention, the mold is horizontally immersed in methanol for at least 4 days, during which the mold is flipped 180° up and down every 2 to 4 hours. The reason is that the composite material molding process is relatively long. During this molding process, the unmolded precursor solution may agglomerate and settle. In order to prevent the precursor solution from settling to one side of the mold due to gravity, resulting in one side of the molded body being dense and the other side being loose, and the overall anti-bending ability is reduced, the present invention flips the mold up and down 180° every 2 to 4 hours. Note: flipping up and down 180° refers to flipping the mold up and down along the diameter direction.
[0053] In the precursor solution of the present invention, the ratio of the total amount of inorganic nanoparticles to hexafluoroisopropanol is 30-40g:100mL; and / or, the hydroxyapatite nanoparticles account for 1wt%-55wt% of the total amount of silk fibroin and inorganic nanoparticles; the silk fibroin accounts for 45wt%-99wt% of the total amount of silk fibroin and inorganic nanoparticles. Preferably, the hydroxyapatite nanoparticles account for 20wt%-30wt% of the total amount of silk fibroin and inorganic nanoparticles; the silk fibroin accounts for 70wt%-80wt% of the total amount of silk fibroin and inorganic nanoparticles. When the ratio of the total amount of inorganic nanoparticles to hexafluoroisopropanol is within the above range, the silk fibroin and inorganic nanoparticles can be completely dissolved; when the weight ratio of silk fibroin and inorganic nanoparticles is within the above range, a composite material that meets the strength requirements can be prepared.
[0054] In some embodiments of the present invention, zinc oxide nanoparticles are used to replace part of the hydroxyapatite nanoparticles, and the composite material has a more excellent osteogenic ability, significantly accelerating bone mineralization and growth; preferably, the zinc oxide nanoparticles account for 1wt% to 5wt% of the total amount of silk protein and inorganic nanoparticles. Nano zinc oxide has excellent antibacterial and osteogenic abilities, and its antibacterial mechanism includes the generation of reactive oxygen species, the release of zinc ions, the inhibition of energy metabolism and the cleavage of bacterial cell walls. Zinc, as a trace element in the human body, plays a vital role in the metabolic process of bone formation. About 30% of zinc in the human body is stored in the bone matrix, and it can also activate bone homeostasis-related proteins. Studies have found that zinc oxide nanoparticles can accelerate bone mineralization and growth. In addition, it has selective toxicity to bacteria and is safe for normal human cells.
[0055] In some embodiments of the present invention, providing a precursor solution includes: adding silk fibroin and inorganic nanoparticles to hexafluoroisopropanol, mixing and standing in an environment of 50 to 60°C for more than 0.5h, waiting for the solid to completely dissolve and the bubbles to escape, to obtain a precursor solution. Standing the mixed solution in an environment of 50 to 60°C for more than 0.5h can ensure that the solid is completely dissolved and the bubbles are completely escaped, thereby obtaining a uniform precursor solution, and then obtaining a uniform composite material.
[0056] In some embodiments of the present invention, the precursor solution further comprises a functional factor, which is one or more of zinc oxide, curcumin, vancomycin, astragalus polysaccharide, and gentamicin, and the weight percentage of the functional factor in the silk fibroin / hydroxyapatite composite material is 0.1% to 5%. The present invention adds functional factors to the precursor so that the composite material obtains functions other than mechanical functions. After adding curcumin, the composite material has excellent broad-spectrum antibacterial properties and anti-tumor effects. Curcumin is a phenolic compound extracted from turmeric, a plant of the ginger family. It has good biocompatibility, anti-tumor, immunomodulatory activity, anti-inflammatory and antioxidant effects, can promote osteosarcoma cell apoptosis, and will not hinder bone regeneration. Curcumin reduces bone resorption by inhibiting the formation of osteoclasts, and can also promote osteoblastic differentiation, thereby increasing bone density.
[0057] In some embodiments of the present invention, after removing the mold, the organic solvent can be completely removed by soaking the formed body in pure water for 7 days. In order to improve production efficiency under the condition of completely removing the organic solvent, the soaking time is preferably 7 to 10 days; further, the soaking time is preferably 7 to 8 days.
[0058] Silk fibroin / hydroxyapatite composite material:
[0059] The silk fibroin / hydroxyapatite composite material prepared by the above-mentioned silk fibroin / hydroxyapatite composite material preparation method of the present invention can produce a 150 mm long bone nail with a three-point bending strength of 235N and a tensile breaking strength of 153MPa, and its mechanical properties are significantly better than those of the hydroxyapatite / silk fibroin bone nail prepared by the existing molding method.
[0060] application:
[0061] The silk fibroin / hydroxyapatite composite material prepared by the above-mentioned silk fibroin / hydroxyapatite composite material preparation method of the present invention can be used to make bone repair parts, and the bone repair parts include bone nails, bone plates, wire anchors, etc.
[0062] Example:
[0063] The following are examples of the present invention. The examples described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. Where specific techniques or conditions are not specified in the examples, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0064] Unless otherwise specified, the embodiments of the present invention and the comparative examples all use hydroxyapatite nanoparticles and zinc oxide nanoparticles with a particle size distribution between 60nm and 80nm, and the silk fibroin used is prepared by the following method: crushing and grinding the silk cocoons, and using sodium carbonate aqueous solution to steam and degumming for 0.5h; dissolving the dried silk in 9.3mol / L lithium bromide solution; dialyzing the solution with distilled water for 3 days, freeze-drying, and obtaining a white foamy silk fibroin sample; using a pulverizer to grind the silk fibroin sample into a silk fibroin powder with a particle size of less than 0.25mm. The dialysis membrane uses a regenerated cellulose dialysis membrane with a molecular weight cutoff of 10kDa. The peristaltic pressurizing device is a peristaltic pump. The mold used in the following embodiments is a commercially available ordinary 20mm×150mm polyethylene flat-mouth test tube, and the soft porous plug is a commercially available ordinary sponge plug.
[0065] Example 1
[0066] The preparation method of the silk fibroin / hydroxyapatite composite material provided in this embodiment comprises the following steps:
[0067] (1) Take 5 g of silk fibroin powder, add hydroxyapatite nanoparticles, and mix them evenly using a vortex mixer and an ultrasonic oscillator to obtain a mixture; wherein the hydroxyapatite nanoparticles account for 25 wt % of the mixture.
[0068] (2) The mixture was uniformly dispersed in hexafluoroisopropanol at a rate of 33 g per 100 mL of hexafluoroisopropanol, and kept in an oven at 55° C. for 0.5 h to completely dissolve the hydroxyapatite nanoparticles and silk fibroin. The mixture was kept warm until the bubbles floated up and completely escaped, thereby obtaining a precursor solution 1.
[0069] (3) The precursor solution 1 is taken out from the drying oven, 5 g of silk fibroin powder and hydroxyapatite nanoparticles of the same mass as in step (1) are added thereto, and after mixing, an equal volume of hexafluoroisopropanol as in step (2) is added and mixed, and the mixture is kept warm in an oven at 55° C. for 0.5 h to remove bubbles, thereby obtaining a precursor solution 2.
[0070] (4) Repeat step (3) three times to obtain a sufficient amount of precursor solution.
[0071] (5) At 55°C, the precursor solution was slowly injected into the long cylindrical mold, and a sponge plug wrapped with a dialysis membrane was inserted into the opening of the long cylindrical mold (see Figure 1 ). The long cylindrical mold was horizontally immersed in methanol, and then a peristaltic pump was used to apply constant pressures of different sizes (0, 1N, 10N, 20N, 30N, 40N, 50N) to the sponge plug (see Figure 2 ), and let it stand for 5 days, during which the mold was turned 180° up and down every 2 hours.
[0072] (6) The molded body was poured out of the mold, and immersed in pure water for 7 days to remove the residual hexafluoroisopropanol and methanol solvents. After natural air drying, a hydroxyapatite / silk fibroin composite material was obtained.
[0073] Example 2
[0074] The only difference between this embodiment and embodiment 1 is that zinc oxide nanoparticles are used in the precursor solution to replace part of the hydroxyapatite nanoparticles, the zinc oxide nanoparticles account for 3wt% of the sum of the silk fibroin powder, the hydroxyapatite nanoparticles and the zinc oxide nanoparticles, and the hydroxyapatite nanoparticles account for 22%.
[0075] The preparation method of the silk fibroin / hydroxyapatite composite material provided in this embodiment comprises the following steps:
[0076] (1) Take 5 g of silk fibroin powder, add hydroxyapatite nanoparticles and zinc oxide nanoparticles, and mix them evenly using a vortex mixer and an ultrasonic oscillator to obtain a mixture; wherein the hydroxyapatite nanoparticles account for 22 wt % of the mixture, and the zinc oxide nanoparticles account for 3 wt % of the mixture.
[0077] (2) The mixture was uniformly dispersed in hexafluoroisopropanol at a rate of 33 g per 100 mL of hexafluoroisopropanol, and kept in an oven at 55° C. for 0.5 h to completely dissolve the hydroxyapatite nanoparticles and silk fibroin. The mixture was kept warm until the bubbles floated up and completely escaped, thereby obtaining a precursor solution 1.
[0078] (3) The precursor solution 1 is taken out from the drying oven, and 5 g of silk fibroin powder and hydroxyapatite nanoparticles and zinc oxide nanoparticles of the same mass as those in step (1) are added thereto. After mixing, an equal volume of hexafluoroisopropanol as in step (2) is added and mixed. The mixture is kept warm in an oven at 55° C. for 0.5 h to remove bubbles, thereby obtaining a precursor solution 2.
[0079] (4) Repeat step (3) three times to obtain a sufficient amount of precursor solution.
[0080] (5) At 55°C, the precursor solution was slowly injected into the long cylindrical mold, and a sponge plug wrapped with a dialysis membrane was inserted into the opening of the long cylindrical mold (see Figure 1 ). The long cylindrical mold was immersed horizontally in methanol, and then a peristaltic pump was used to apply a 30N pressure to the sponge plug (see Figure 2 ), and let it stand for 5 days, during which the mold was turned 180° up and down every 2 hours.
[0081] (6) The molded body was poured out of the mold, and immersed in pure water for 7 days to remove the residual hexafluoroisopropanol and methanol solvents. After natural air drying, a hydroxyapatite / silk fibroin composite material was obtained.
[0082] Comparative Example 1
[0083] The only difference between this comparative example and Example 1 is that no peristaltic pump is used to apply 30N pressure to the sponge plug.
[0084] The preparation method of the silk fibroin / hydroxyapatite composite material provided in this comparative example comprises the following steps:
[0085] (1) Take 5 g of silk fibroin powder, add hydroxyapatite nanoparticles, and mix them evenly using a vortex mixer and an ultrasonic oscillator to obtain a mixture; wherein the hydroxyapatite nanoparticles account for 25 wt % of the mixture.
[0086] (2) The mixture was uniformly dispersed in hexafluoroisopropanol at a rate of 33 g per 100 mL of hexafluoroisopropanol, and kept in an oven at 55° C. for 0.5 h to completely dissolve the hydroxyapatite nanoparticles and silk fibroin. The mixture was kept warm until the bubbles floated up and completely escaped, thereby obtaining a precursor solution 1.
[0087] (3) The precursor solution 1 is taken out from the drying oven, 5 g of silk fibroin powder and hydroxyapatite nanoparticles of the same mass as in step (1) are added thereto, and after mixing, an equal volume of hexafluoroisopropanol as in step (2) is added and mixed, and the mixture is kept warm in an oven at 55° C. for 0.5 h to remove bubbles, thereby obtaining a precursor solution 2.
[0088] (4) Repeat step (3) three times to obtain a sufficient amount of precursor solution.
[0089] (5) At 55°C, the precursor solution was slowly injected into the long cylindrical mold, and a sponge plug wrapped with a dialysis membrane was inserted into the opening of the long cylindrical mold (see Figure 1 ). The long cylindrical mold was immersed in methanol horizontally and left to stand for 5 days, during which the mold was turned upside down 180° every 2 hours.
[0090] (6) The molded body was poured out of the mold, and immersed in pure water for 7 days to remove the residual hexafluoroisopropanol and methanol solvents. After natural air drying, a hydroxyapatite / silk fibroin composite material was obtained.
[0091] Comparative Example 2
[0092] The only difference between this comparative example and Example 2 is that no peristaltic pump is used to apply 30N pressure to the sponge plug.
[0093] The preparation method of the silk fibroin / hydroxyapatite composite material provided in this comparative example comprises the following steps:
[0094] (1) Take 5 g of silk fibroin powder, add hydroxyapatite nanoparticles and zinc oxide nanoparticles, and mix them evenly using a vortex mixer and an ultrasonic oscillator to obtain a mixture; wherein the hydroxyapatite nanoparticles account for 22 wt % of the mixture, and the zinc oxide nanoparticles account for 3 wt % of the mixture.
[0095] (2) The mixture was uniformly dispersed in hexafluoroisopropanol at a rate of 33 g per 100 mL of hexafluoroisopropanol, and kept in an oven at 55° C. for 0.5 h to completely dissolve the hydroxyapatite nanoparticles and silk fibroin. The mixture was kept warm until the bubbles floated up and completely escaped, thereby obtaining a precursor solution 1.
[0096] (3) The precursor solution 1 is taken out from the drying oven, and 5 g of silk fibroin powder and hydroxyapatite nanoparticles and zinc oxide nanoparticles of the same mass as those in step (1) are added thereto. After mixing, an equal volume of hexafluoroisopropanol as in step (2) is added and mixed. The mixture is kept warm in an oven at 55° C. for 0.5 h to remove bubbles, thereby obtaining a precursor solution 2.
[0097] (4) Repeat step (3) three times to obtain a sufficient amount of precursor solution.
[0098] (5) At 55°C, the precursor solution was slowly injected into the long cylindrical mold, and a sponge plug wrapped with a dialysis membrane was inserted into the opening of the long cylindrical mold (see Figure 1 ). The long cylindrical mold was immersed horizontally in methanol, and then a peristaltic pump was used to apply a 30N pressure to the sponge plug (see Figure 2 ), and let it stand for 5 days, during which the mold was turned 180° up and down every 2 hours.
[0099] (6) The molded body was poured out of the mold, and immersed in pure water for 7 days to remove the residual hexafluoroisopropanol and methanol solvents. After natural air drying, a hydroxyapatite / silk fibroin composite material was obtained.
[0100] Performance Test:
[0101] The cylindrical silk fibroin / hydroxyapatite composite rods prepared in the above embodiments and comparative examples are turned into semi-threaded screws by precision CNC machine tools. Figure 3 shown.
[0102] The three-point bending of the semi-threaded screws was tested using a universal material testing machine. The specific test steps were based on the YY / T0509-2009 "Standard Requirements and Test Methods for Bioabsorbable Internal Fixation Plates and Screws". The results are as follows: Figure 4 , Figure 5 shown.
[0103] like Figure 4 As shown, the mechanical properties of the silk fibroin / hydroxyapatite composite material prepared in Example 1 under a constant thrust of less than 30N are poor, while when the constant thrust is greater than 30N, the mechanical properties of the prepared silk fibroin / hydroxyapatite composite material are greatly improved, the three-point bending strength can reach 235N, and the tensile fracture strength can reach 153MPa.
[0104] like Figure 5 As shown, after zinc oxide nanoparticles were used in Example 2 to partially replace the hydroxyapatite nanoparticles in Example 1, there was no significant difference in the performance of the composite material, indicating that zinc oxide nanoparticles can be used to partially replace hydroxyapatite nanoparticles to accelerate bone mineralization and growth and play an antibacterial role.
[0105] The hydroxyapatite / silk fibroin composite material prepared in Example 1 under a constant thrust of 30 N was observed using a scanning electron microscope, and it was found that the composite material prepared under this condition had a dense and less porous structure, which also explains why the composite material prepared in the present invention has higher mechanical properties.
[0106] Figure 7 The antibacterial rate of the hydroxyapatite / silk fibroin composite material prepared in Example 2 is shown. It can be seen that after the zinc oxide nanoparticles in Example 2 partially replace the hydroxyapatite nanoparticles in Example 1, the composite material has an antibacterial function.
[0107] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a silk fibroin / hydroxyapatite composite material, characterized in that: The steps include: Providing a precursor solution; the precursor solution consists of inorganic nanoparticles, silk fibroin and hexafluoroisopropanol; the inorganic nanoparticles are hydroxyapatite nanoparticles or a mixture of hydroxyapatite nanoparticles and zinc oxide nanoparticles; The precursor solution is poured into a long cylindrical mold with one end open and the other end closed, and then the open end of the mold is sealed with a soft porous plug wrapped with a dialysis membrane; The mold is horizontally immersed in methanol for at least 4 days, during which a constant thrust of 30 to 300 N is applied to the porous plug wrapped with the dialysis membrane, the soft porous plug wrapped with the dialysis membrane is evenly and slowly pushed into the mold, and the mold is turned upside down 180 degrees every 2 to 4 hours to obtain a molded body; The mold is removed, and the molded body is immersed in pure water for at least 7 days. After drying at room temperature, a silk fibroin / hydroxyapatite composite material is obtained.
2. The method for preparing the silk fibroin / hydroxyapatite composite material according to claim 1, characterized in that: The molecular weight cut-off of the dialysis membrane is 5 to 15 kDa.
3. The method for preparing the silk fibroin / hydroxyapatite composite material according to claim 1, characterized in that: The constant thrust is 30-50N.
4. The method for preparing the silk fibroin / hydroxyapatite composite material according to claim 1, characterized in that: In the precursor solution, the ratio of the total amount of inorganic nanoparticles to hexafluoroisopropanol is 30-40 g:100 mL; and / or, The hydroxyapatite nanoparticles account for 1 wt% to 55 wt% of the total amount of the silk fibroin and the inorganic nanoparticles; the silk fibroin accounts for 45 wt% to 99 wt% of the total amount of the silk fibroin and the inorganic nanoparticles.
5. The method for preparing the silk fibroin / hydroxyapatite composite material according to claim 4, characterized in that: The hydroxyapatite nanoparticles account for 20 wt% to 30 wt% of the total amount of the silk fibroin and the inorganic nanoparticles; the silk fibroin accounts for 70 wt% to 80 wt% of the total amount of the silk fibroin and the inorganic nanoparticles.
6. The method for preparing the silk fibroin / hydroxyapatite composite material according to claim 1 or 4, characterized in that: The precursor solutions provided include: Silk fibroin and inorganic nanoparticles are added to hexafluoroisopropanol, mixed and allowed to stand for more than 0.5 h in an environment of 50-60° C., and bubbles are removed after the solid is completely dissolved to obtain a precursor solution.
7. The method for preparing the silk fibroin / hydroxyapatite composite material according to claim 1, characterized in that: The particle size of the hydroxyapatite nanoparticles is 60-80 nm; the particle size of the silk fibroin is 0.1-1.5 mm.
8. The method for preparing the silk fibroin / hydroxyapatite composite material according to claim 1, characterized in that: The precursor solution also contains functional factors, which are one or more of curcumin, vancomycin, astragalus polysaccharide, and gentamicin. The weight percentage of the functional factors in the silk fibroin / hydroxyapatite composite material is 0.1% to 5%.
9. A silk fibroin / hydroxyapatite composite material, characterized in that: The silk fibroin / hydroxyapatite composite material is prepared by the preparation method of any one of claims 1 to 8.
10. Use of the silk fibroin / hydroxyapatite composite material according to claim 9 in preparing bone repair parts.
Citation Information
Patent Citations
Silk fibroin / hydroxyapatite composite material as well as preparation method and application thereof
CN113332498A
Cited By
Method for compositing inorganic mineral and protein
WO2026200449A1
